MULTILITERATION LEARNING IN WRITING ENGLISH DESCRIPTIVE TEXT THROUGH COLLABORATIVE TECHNIQUES – (THEORITICAL REVIEW) - Mayasari, Santi; Firdaus, Masagus; Widayatsih, Tri (Universitas Sebelas Maret, 2018)
Multiliteration Learning through collaborative techniques is one of the study used by teachers and lecturers in disruption era. Disruption era is an era that needs a very rapid change and transforming old things into new and work intense in the world competition, and the movement of the highly developed world industry makes us as teachers or lecturers to be ready to prepare our students in this sophisticated era. Teachers are required to be more creative in delivering classroom learning. Multiliteration learning through collaborative techniques becomes one of the more creative learning alternatives. Multiliteration learning is used to develop the competence of various sources of literacy both visual literacy, multimedia, technology, critical, cross curriculum, as well as various literacy resources that exist around people's lives. In Modern learning using a more attractive and sophisticated facilities that are able to explore the potential and mindset of learners to be more qualified. The teacher will dig the students creative and fun. The benefits of multiliteration learning in Teaching English are; (1) to explore more creative ideas in English descriptive text, (2) to improve the students English grammar; (3) to master the vocabulary in a descriptive text; and (4) to use the best facilities at school to support the development of multiliteration study.